Prenatal Opioid Exposure and Intermittent Hypoxemia in Preterm Infants: A Retrospective Assessment - Abu Jawdeh, Elie G.; Westgate, Philip M.; Pant, Amrita; Stacy, Audra L.; Mamilla, Divya; Gabrani, Aayush; Patwardhan, Abhijit; Bada, Henrietta S.; Giannone, Peter (Frontiers in Pediatrics, 2017)
Abstract Introduction: Intermittent hypoxemia (IH) is defined as episodic drops in oxygen saturation (SpO2). Preterm infants are at increased risk for IH due to their immature respiratory control/apnea of prematurity. The clinical relevance of IH is a relatively new observation with rising evidence linking IH to neonatal morbidities and long term impairment. Hence, assessing factors that influence IH in preterm infants is imperative. Given the epidemic of opioid misuse in the USA, there is an urgent need to understand the impact of prenatal opioid exposure on neonatal outcomes. Hence, we wanted to assess the relationship between isolated prenatal opioid exposure and IH in preterm infants. Methods: In order to accurately calculate IH, SpO2 data were prospectively collected using high resolution pulse oximeters during the first 8 weeks of life in preterm infants less than 30 weeks gestational age. Data related to prenatal opioid misuse were retrospectively collected from medical charts. Infants with tobacco or poly-drug exposure were excluded. The primary outcome measure is percent time spent with SpO2 below 80% (%time-SpO2<80). The secondary outcome measure is the number of severe IH events/week with SpO2 less than 80% (IH-SpO2<80). Results: A total of 82 infants with isolated opioid exposure (n=14) or who were unexposed (n=68) were included. There were no significant differences in baseline characteristics between opioid exposed and unexposed groups. There was a statistically significant increase of 0.23 [95% CI: (0.03, 0.43), p=0.03] in mean of the square root of %time-SpO2<80. The number of IH-SpO2<80 events was higher in the opioid exposed group [mean difference = 2.95, 95% CI: (-0.35, 6.25), p-value = 0.08], although statistical significance was not quite attained. Conclusion: This study shows that preterm infants prenatally exposed to opioids have increased IH measures compared to unexposed infants. Interestingly, the increased IH in the opioid exposed group persists beyond the immediate postnatal period.